Perceptions of Women of Color on Career Advancement in High Technology Management - Charles, Angela Michelle (2017)
In information technology, few women of color hold senior level executive leadership positions in the United States. Currently, in the high-tech industry, Asian and Black women hold 1.7% of executive/senior-level positions, and only 0.2% are in CEO positions. The purpose of this research was to understand professional executive women of color experiences in career advancement in the high technology fields. The study's conceptual framework included organizational culture theory, Krumboltz's theory of career counseling, and the leadership pipeline model. The overarching research question and subquestions addressed the lived experiences of 15 professional senior executive women of color in relation to career advancement in high technology to understand their perceptions, feelings, and values through a transcendental descriptive phenomenological approach. Through the use of Colaizzi's method of data analysis, 8 major themes and 11 subthemes emerged from interviews with the participants. The results indicated that women of color needed to have access to internal opportunities for advancement, adjusting to longer work hours in a male dominated work environment, and the need to establish networks of women of color for support. This study may support positive social change by prompting organizational leaders to develop gender-neutral, comprehensive strategies that do not impede women from obtaining technical executive positions. If women were extended the same opportunities as their senior executive male counterparts, women executives could thrive as senior leaders